PENGARUH GAYA KEPEMIMPINAN SITUASIONAL TERHADAP PENGEMBANGAN KARIR YANG DIMEDIASI OLEH MOTIVASI PADA BIDANG PERSIDANGAN SEKRETARIAT DPRD PROVINSI SULAWESI TENGGARA - Amir Mahmud; Bakhtiar Abbas; Rahmatia (Sigma: Journal of Economic and Business, 2019)
This study was aimed at determining: The effect of situational leadership style on the working motivation, The effect of situational leadership style on career development, The effect of working motivation on career development, The effect of motivation mediated to strengthen the influence of situational leadership style on the career. The object of this study was employee career development in the Field of Trial Parliament Secretariat Southeast Sulawesi Province. The population was all employees who were civil servants, as many as 59 people taken by using census. Data analysis used was descriptive statistics and Partial Least Square (PLS). The results of this study concluded that: Situational leadership style significantly affected on employee motivation; The situational leadership style significantly affected on employee career development, Motivation significantly affected on employee career development, Motivation mediated the influence of situational leadership style to career development